Exploring the effects of task complexity and translation anxiety on EFL learners’ translation performance: Evidence from a mixed-design study - Xiangyan Zhou; Xiaodong Liu (PLoS ONE, 2026)
While the impact of task complexity on translation performance has received considerable attention, relatively little research has explored whether affective factors such as translation anxiety moderate this effect. This study investigated the joint influence of task complexity and translation anxiety on English as a foreign language (EFL) learners’ written translation performance using a 2 × 2 mixed design. A total of 106 EFL learners from diverse disciplines in China participated in the study, with 100 included in the final analyses; their translation anxiety was assessed using a Translation Anxiety Scale adapted for written translation. Participants completed two written translation tasks at different complexity levels. Their translation performance was assessed in terms of process efficiency (i.e., total processing time, subjective cognitive effort, and the number of effective revisions) and product quality (i.e., accuracy, fluency, and analytical quality measures). Linear mixed-effects models showed consistent effects of task complexity on translation performance, whereas translation anxiety played a selective and context-dependent role, mainly by moderating the effects of task complexity on some efficiency outcomes. The study develops a conceptual framework that integrates task-related factors and learner factors as predictors of translation performance and offers pedagogical insights for translation teaching.